The very hungry caterpillar - Carle, Eric (Philomel Books, 1967)
The book talks about the process of caterpillars hatching. It was a sunny Sunday when the caterpillar emerged from a small egg. He was very hungry. On Monday, he ate an entire apple; On Tuesday, he ate all three seasons of Plums - but he was still hungry. Bold, colorful images and simple text with large, clear text tell the story of a thirsty little caterpillar's development through an astonishing variety and quantity of food. He eventually made a cocoon around himself and went to sleep, to wake up a few weeks later wonderfully transformed into a butterfly!